PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1954)
This article presents an account of questions prepared by the Board of Examiners of the American Institute of Accountants that were presented as the second half of the C.P.A. examination in accounting practice on November 5, 1953. The candidates were required to solve all problems in four and a half hours. The weights assigned were: problem 1, 12 points; problem 2, 8 points; problem 3, 30 points. Questions relate to federal income taxes were also in the examination. Parts (a) and (b), dealt with items of gross income and deductions, respectively, and were to be answered true or false. However, in not more than one sentence, a candidate was allowed to give the reason for the conclusion where an explanation seemed appropriate. The merit of the explanation was to be considered if given. The first question required candidates to prepare journal entries to record at December 31, 1952 the recognition of profits and any other adjustments arising from the data provided for a given company. Secondly, to give complete explanations in support of entries and Give one acceptable alternate method of handling the repossession and discuss merits of it.